Majority voting and the welfare implications of tax avoidance - Christian Traxler (Max Planck Institute for Research on Collective Goods, 2009)
A benchmark result in the political economy of taxation is that majority voting over a linear income tax schedule will result in an inefficiently high tax rate whenever the median voter has a below average income. The present paper examines the role of tax avoidance for this welfare assessment. We find that the inefficiency in the voting equilibrium is the lower, the higher the average level of tax avoidance in the economy, or equivalently, the lower the median voter's amount of avoidance. The result holds for endogenous avoidance and labor choice and, under certain conditions, for an endogenous enforcement policy.
Keywords: H26; D72; D6; 330; Tax avoidance; welfare analysis; majority voting; median voter equilibrium; Steuervermeidung; Wohlfahrtseffekt; Einkommensteuertarif; Einkommensteuerpolitik; Median Voter; Steuerwirkung; Theorie